Apical right ventricular dysfunction in patients with pulmonary hypertension demonstrated with magnetic resonance. Issue 15 (14th June 2011) - Fernandez-Friera, Leticia; Garcia-Alvarez, Ana; Guzman, Gabriela; Bagheriannejad-Esfahani, Fatemeh; Malick, Waqas; Nair, Ajith; Fuster, Valentin; Garcia, Mario J; Sanz, Javier
Abstract : Objective: To evaluate segmental right ventricular (RV) dysfunction in pulmonary hypertension (PH) using cardiac magnetic resonance (CMR). Design: Cross-sectional analysis in a retrospective cohort of consecutive adult patients. Setting: Mount Sinai Hospital in New York. Patients: 192 patients with known or suspected PH undergoing right heart catheterisation and CMR. PH was defined as mean pulmonary artery pressure ≥25 mm Hg. Abnormal RV ejection fraction (RVEF) was defined as <50%. Patients were classified into: group 1 (no PH, normal RVEF; n=40), group 2 (PH, normal RVEF; n=41) or group 3 (PH, abnormal RVEF; n=111). Interventions: CMR and right heart catheterisation within a 2-week interval. Main outcome measures: On cine CMR images, the stack of RV short-axis views was divided into two equal halves. Basal and apical RVEF were calculated using Simpson's method, and a ratio of basal-to-apical RVEF (RVEFratio ) was derived. Results: Basal RVEF did not differ between groups 1 and 2 (63±8% vs 64±8%; p=1); however, patients in group 2 had significantly lower apical RVEF (46±13% vs 58±10%; p<0.01) and higher RVEFratio (median 1.4 vs 1.1; p<0.01). Both apical and basal RVEF were reduced in group 3 compared with groups 1 and 2 (p<0.01), and the RVEFratio increased with increasing PH severity (p<0.01 for trend). An apical RVEF <50% was more sensitive than global RV dysfunction for the detection of PH. Conclusions: Apical dysfunction appears to occur before global RVEF decreases in chronic PH, potentially constituting an early and sensitive marker of RV dysfunction in this setting.